Peran Badan Narkotika Provinsi Nusa Tenggara Barat dan Polisi Resort Kota Mataram Dalam Menanggulangi Pengedaran dan Penyalahgunaan Narkoba - Syamsul Hidayat (Jatiswara, 2016)
Drug trafficking is very disturbing society. Not only teenagers and young adults who fall in drug use, but also parents who in fact should be understood the dangers of drugs. Focus issues raised this study the role of the National Narcotics Agency of West Nusa Tenggara and Police Resort Kota Mataram in tackling trafficking and drug abuse. These results indicate that the role of the National Narcotics Agency West Nusa Tenggara Province in tackling drug trafficking and abuse and consists of: Supply control is an integrated effort negate the availability of narcotics in the market or in the community. Demand reduction is an integrated effort that is rehabilitative and. Harm reduction is an effort by the activities of a rehabilitative intervention to victims or users who have ketergantungan.Upaya Mataram Police in tackling the narcotics criminal offense in Mataram emphasize the prevention without the use of criminal law, prevention is done by the method of legal counseling, awareness and also education of the public.